Luminescence Database I—Minerals and Materials - MacRae, Colin M.; Wilson, Nicholas C. (Microscopy and microanalysis, 2008)
A luminescence database for minerals and materials has been complied from the literature, the aim being to create a resource that will aid in the analysis of luminescence spectral of ionic species in minerals and materials. The database is based on a range of excitation techniques and records both major and minor lines, and their activators. The luminescence techniques included in the database are cathodoluminescence, ion luminescence, and photoluminescence. When combined with other traditional X-ray measurements collected on the same region, use of the luminescence database will give additional insight into the chemistry of minerals and materials.